Experimental characterization of a quasi-coherent turbulent structure in the edge plasma in Wendelstein 7-X. (31st October 2019) - Han, X.; Krämer-Flecken, A.; Windisch, T.; Hirsch, M.; Fuchert, G.; Geiger, J.; Grulke, O.; Liu, S.; Rahbarnia, K.
Abstract: A quasi-coherent mode (QCM) near the plasma edge is characterized experimentally by measuring the density fluctuation via a poloidal correlation reflectometer (PCR) in Wendelstein 7-X. This QCM frequency descends from 25 kHz near the separatrix to 10 kHz as the cutoff position penetrates toward the core. A similar mode structure is also observed in the spectra of electron cyclotron emission edge channels and Mirnov coil signals, which shows a clear correlation with respect to the PCR measurement. The mode evaluation yields a range for the poloidal mode number of, and for the normalized mode scale, which suggest a drift type instability. The QCM structure appears in the standard and narrow-mirror configurations (both with the rotational transform in the boundary), but is absent in the high- configuration (boundary ). The impact of plasma parameters on the QCM is discussed. It is observed that the QCM frequency and amplitude can be affected by the edge magnetic topology and plasma parameters. The shifts upward during the negative and non-stellarator-symmetric control coil current scans, which may be attributed to the effect of the shear, E r, and n e in the plasma edge region.